2017
DOI: 10.5334/jime.433
|View full text |Cite
|
Sign up to set email alerts
|

Using Digital Concept Maps to Distinguish Between Young Refugees’ Challenges

Abstract: Digital media are beneficial for research of complex refugee issues, as they allow refugees to express their personal experiences of complex issues in ways that are not restricted by language barriers or limited in authenticity, while also offering researchers a way to systematically compare refugees' varied experiences. We used a computerised concept mapping task to ask 74 young refugees (teenagers and young adults), from three separately recruited samples, to think about their experiences with various challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Moreover, in China Nie et al (2020) found an association between smartphone use and increases in both life satisfaction and happiness. M-Learning has been utilized to relate education to immigrants' physical contexts in a process of providing them with access to location-specific language materials such as expressions that could be useful in everyday interactions (Godwin-Jones, 2018;Brooker et al, 2017;Andrade and Doolin, 2016;Jarvis and Orr, 2016;Gillespie et al, 2018;Pegrum, 2014;Kukulska-Hulme, 2009). In the UK, Spain and Austria Kukulska-Hulme et al (2015) found that language applications supported immigrants' personalized learning (Kukulska-Hulme et al, 2015).…”
Section: M-integration Applications In Relation To Public Services Communication and Educationmentioning
confidence: 99%
“…Moreover, in China Nie et al (2020) found an association between smartphone use and increases in both life satisfaction and happiness. M-Learning has been utilized to relate education to immigrants' physical contexts in a process of providing them with access to location-specific language materials such as expressions that could be useful in everyday interactions (Godwin-Jones, 2018;Brooker et al, 2017;Andrade and Doolin, 2016;Jarvis and Orr, 2016;Gillespie et al, 2018;Pegrum, 2014;Kukulska-Hulme, 2009). In the UK, Spain and Austria Kukulska-Hulme et al (2015) found that language applications supported immigrants' personalized learning (Kukulska-Hulme et al, 2015).…”
Section: M-integration Applications In Relation To Public Services Communication and Educationmentioning
confidence: 99%
“…Among the various difficulties that refugees encounter during their journey, language presents a primary challenge (Brooker et al 2017). Refugees use different language learning methods depending on their location and the resources available to them.…”
Section: Refugees and Language Learningmentioning
confidence: 99%